THE EFFECT OF USING MIND MAPPING ON READING COMPREHENSION OF THE FIRST YEAR STUDENTS OF SMAN PLUS RIAU - Rahmi Vilia Gustin; Syofia Delfi; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental research was aimed at finding out whether there is a significant effect of using Mind Mapping on reading comprehension of the first year students of SMAN PLUS RIAU. The research model was one group pretest-posttest design. The population were the first year students in academic year of 2016/2017. The sample was 24 students out of the population, chosen by using cluster sampling. The data were collected by administering a reading comprehension test concerning narrative texts. The collected data were analyzed by using SPSS version 23.0. The finding of the reseacrh showed that the mean score of post-test was higher than that of pre-test (80.67>70.81). The value of t-test was higher than t-table (19.49>2.06)at 5% of the significant level. Therefore, alternative hyphothesis (Ha) was accepted. It means that mind mapping was effective for teaching reading comprehension especially on narrative texts. The implication of the finding was that the use of mind mapping in increasing the level of reading comprehension.Keywords: Mind Mapping, Reading Comprehension, Narrative Texts